(untitled) (GYMNASIUM, 2017)
Figure skating is a winter sport that consists in the execution of specific elements such as jumps, pirouettes and steps on a surface covered by ice in the presence of musical accompaniment. High performance in figure skating in Romania can only be obtained by a program that combines off ice training with on ice training. In the present study we aimed to increase the sports results of a group of six young skaters due to improving overall coordination and spatial awareness by applying an experimental program of specific gymnastics exercises in skater straining. The results were highlighted by applying Matorini test, a test of spatial orientation and by the statistical analysis of the results obtained in sheets of observations from official national competitions.